Impact of Shareholders Conflict on Market Capitalization: Example of Vimpelcom - Елена Владимировна Чиркова; И. В. Мороз; Юрий Яковлевич Дранев (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2014)
Authors: Victoria A. Cherkasova National Research University The Higher School of EconomicsYuri Y. Dranev National Research University The Higher School of Economics dranioff@hotmail.comShareholder conflict may significantly impact market capitalization of a firm because of rising risk of additional reputational costs. In this paper we analyze changes in value of Russina telecommunication company Vimpelcom after mass media announcements about developments in lawsuits between major shareholders in 2005-2013. We suggest methodology of prediction of market reaction. All announcements are classified according to several characteristics. Calculation of abnormal return allowed us to estimate cumulative losses of shareholders of Vimpelcom due to the conflict between Altimo and Telenor.